Shifts in Campylobacter species abundance may reflect general microbial community shifts in periodontitis progression - Henne, Karsten (J Oral Microbiol, 2014)
BACKGROUND: Oral Campylobacter species have been found to be associated with periodontitis progression. While the etiological significance of Campylobacter rectus is quite established, the association of C. gracilis, C. concisus, and C. curvus with health or disease remains contradictory. OBJECTIVES: This study hypothesizes that the proportion of species within the Campylobacter genus rather than the absolute abundance of a single species is a suitable indicator for periodontitis progression. DESIGN: Subgingival plaque from 90 periodontitis patients and gingival sulcus fluid of 32 healthy individuals were subjected to a newly developed nested PCR approach, in which all Campylobacter spp. were amplified simultaneously. The resulting mixture of 16S-rRNA-gene-amplicons were separated by single-stranded conformation polymorphism (SSCP) gel electrophoresis, followed by sequencing and identification of excised bands and relative quantification of band intensities. In all samples, the abundance of selected periodontitis marker species was determined based on DNA hybridization on a microarray. RESULTS: The highly prevalent Campylobacter community was composed of varying proportions of C. rectus, C. gracilis, C. concisus, and C. curvus. Cluster analysis based on SSCP-banding pattern resulted in distinct groups which in turn coincided with significant differences in abundance of established periodontitis marker species (Tannerella forsythia, Porphyromonas gingivalis, and Fusobacterium nucleatum) and progression. CONCLUSIONS: The shift in the Campylobacter community composition seems to display the general microbial community shift during clinical progression in a simplified manner. The focus on members of the Campylobacter in this study suggests that this genus can be an indicator of ecological changes in the subgingival oral microflora.